Eficiencia de las prácticas agrícolas en la producción del cultivo de arroz (Oryza sativa L.) - Aldaz Vega, Omar Orlando (2024)
This article describes the effectiveness of agricultural practices in the production of rice crops (Oryza sativa L.). The conclusions determine that it is necessary to integrate organic material from the waste of the previous harvest of soybean cultivation. Depending on the properties of the soil and its depth, a decision will be made between plowing and raking or just discing. It is recommended to avoid overpreparing the soil, as this can deteriorate its structure. Success lies in preventing the germination of weed seeds such as bindweed, milkweed, wild oats, ryegrass, Palmer amaranth, pigweed, papaya and purslane; as well as sedges such as nutsedge, yellow nutsedge and purple nutsedge. It is important to note that weeds have the potential to decrease crop yields by up to 80%. For effective weed management, it is recommended to apply 3 L of Prowl (Pendimentalin) and 3 L of Bolero (benthiocarb) in 200 L of water per hectare immediately after sowing. Prior to application, it is necessary to calibrate the fumigation equipment in order to establish the optimal amount of water to use. Regarding nutritional requirements, it is advisable to apply a dose of 125 kilograms per hectare of nitrogen. Thirty kilograms per hectare of phosphorus oxide and 50 kg/ha of potassium in the form of oxide. Effective management of insect pests and diseases requires identification of insect species and pathogens (such as fungi) to facilitate application of the appropriate pesticide. Carry out the collection according to the state of maturity of the harvest.